Зниження техногенного навантаження на об'єкти довкілля як складова концепції "зеленої економіки" - Галаган, Тетяна Іванівна; Galagan, Tatyana (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2024)
Визначено, що удосконалення системи управління відходами є одним із ключових напрямів розвитку "зеленої"економіки. Екологізація економіки передбачає економічне зростання у поєднанні з екологічною стійкістю, щосприяє підвищенню добробуту людей при одночасному зниженні ризиків для довкілля та стану екологічних ресурсів. Встановлено, що невід'ємною частиною проблеми раціонального використання природних багатств і захисту навколишнього середовища є рекультивація природно-техногенних комплексів та подальше освоєння таких територій, що порушуються під час техногенного навантаження. Доведено, що пріоритетною формою раціонального землекористування як стратегічного напряму розвитку"зеленої економіки" є природоL і ресурсозберігаюча технологія, коли людина і екосистема "земля" перебувають в гармонійній єдності і взаємозв'язку, нащадкам залишаються не пустирі та яри, а високопродуктивні землі, що можливо досягти через відповідні зміни у земельних відносинах. This article deeply analyzes the role of agribusiness within the framework of the "green economy" concept and its strategic alignment towards achieving sustainable development. It aims to explore how contemporary trends in the agricultural sector can be adapted and addressed within the requirements of the "green economy" to create a sustainable and environmentally responsible agricultural system. The model of the "green economy" envisions economic growth combined with environmental sustainability. Since ancient times, humanity has regarded the earth with great respect, as it provides everything necessary for life. However, it also demands sensitive and respectful treatment in return. This is evidenced by numerous historical facts from ancient Ukrainian history, which boasts some of Europe's richest black soils in its land fund. Improving waste management systems is a key direction in the development of the "green" economy. The greening of the economy involves economic growth combined with environmental sustainability, contributing to increased prosperity while simultaneously reducing risks to the environment and ecological resources. An integral part of the problem of rational use of natural resources and environmental protection is the reclamation of natural technogenic complexes and further development of territories disturbed during mineral resource extraction. Technogenic loads in Ukraine and beyond are concentrated in densely populated regions, negatively impacting the natural environment and people's health, reducing their life expectancy. To improve this situation, it is essential to understand that in modern conditions, Ukraine's food security depends on economic independence, the stability and sustainability of land use, and its ability to self develop and progress. Choosing the right path to address land issues and establishing a system of effective land management and land use planning are particularly crucial for Ukraine. The country holds a leading position in Europe in terms of the area of agricultural land and the natural fertility of its soils. A prioritized form of rational land use as a strategic direction for the development of the "green economy" is nature and resource saving technology. This approach aims to harmoniously unite human activities with the ecosystem, ensuring that high productivity lands are left for future generations. Achieving this requires appropriate changes inland relations.
Reduction of technogenic load on environmental objects as a component of the "green economy" concept
Keywords: "зелена економіка"; "green economy"; екологічна стійкість; environmental sustainability; відходи; waste; навколишнє середовище; environment; раціональне землекористування; rational landuse